Pengembangan Media Pembelajaran Papan Bingo pada Materi Perkalian dan Pembagian Pecahan Kelas V SDN 03 Montong Beter - Hulwatul Faizati; Siti Istiningsih; Lalu Sirajul Hadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to develop a bingo board learning media for fraction material and determine its feasibility and practicality in elementary school learning. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The bingo board media was designed to create an interactive and enjoyable learning atmosphere that could improve students’ understanding of fractions. The feasibility of the product was evaluated by media experts and material experts, while practicality was measured through teacher and student responses. The validation results from media experts obtained a percentage score of 94.73%, categorized as “very feasible,” while material expert validation achieved 88.57%, also categorized as “very feasible.” Furthermore, teacher responses reached 97.33% and student responses achieved 99.04%, both included in the “very good” category. These findings indicate that the bingo board learning media is highly valid, practical, and suitable for use in mathematics learning, particularly in fraction material. Therefore, the developed media can be utilized as an innovative learning tool to support engaging and effective classroom instruction for elementary school students.